Pengaruh Sistem Pengendalian Internal, Ketaatan Aturan, Asimetri Informasi Terhadap Kecenderungan Kecurangan Akuntansi (Studi Kasus pada Koperasi di Kota Jayapura) - Sagala, Febriana; Asnawi, Meinarni; Matani, Cornelia D.; Patma, Kurniawan; Sesa, Pascalina V. S.; Paru, Sara M. (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2025)
The research aims to explain the influence of internal control systems, rule compliance and information asymmetry on the tendency of accounting fraud using purposive sampling as a sample collection technique. The population in this study were 19 cooperatives in the city of Jayapura with a sample of 68 respondents. The data used in this research uses a questionnaire which is distributed directly to cooperative members based on predetermined criteria. This research uses Structural Equation Modeling (SEM)-Partial Least Square (PLS) using WarpPLS 8.0 software. The research results show that internal control variables have a negative effect on the tendency for accounting fraud, while rule compliance and information asymmetry have no influence on the tendency for accounting fraud in cooperatives in Jayapura City.Keywords: internal control system, compliance with rules, information asymmetry, accounting fraud tendencies